Could corporate credit losses turn out higher than expected? - Mikael Juselius; Nikola A. Tarashev (Bank of Finland, 2021)
While corporate credit losses have been low since the start of the Covid-19 pandemic, their future evolution is quite uncertain. Using a forecasting model with a solid track record, we find that the baseline scenario ("expected losses") is benign up to 2024. This is due to policy support measures that have kept debt service costs low. However, high indebtedness, built up when the pandemic impaired real activity, suggests increased tail risks: plausible deviations from the baseline scenario ("unexpected losses") feature ballooning corporate insolvencies. Taken at face value, the low expected loss forecasts are consistent with low bank provisions, whereas the high unexpected loss forecasts call for substantial capital.
urn:nbn:fi:bof-202108181391
Keywords: E44; E47; E65; G17; G21; 330; COVID-19